THE INFLUENCE OF LEADERSHIP AND WORK ENVIRONMENT ON WORK MOTIVATION OF EMPLOYEES AT THE TANAH DATAR REGENCY TRANSPORTATION SERVICE - Putri, Yane; Juwita, Patrisia; Aima, M. Havidz; Yulasmi, Yulasmi (Gapenas Publisher, 2025)
This study aims to analyze the influence of leadership and work environment on employee work motivation at the Tanah Datar Regency Transportation Office. The research approach used is associative quantitative with a sample of 60 employees taken using total sampling technique. Data collection was carried out through questionnaires compiled based on the indicators of each variable, and analyzed by multiple linear regression using the SPSS version program. The results of the study indicate that: (1) leadership has a positive and significant effect on employee work motivation, (2) the work environment has a positive and significant effect on employee work motivation, and (3) simultaneously, leadership and work environment have a significant effect on employee work motivation. These findings strengthen the view that employee work motivation in government organizations is greatly influenced by the leadership style applied and the conditions of the work environment created. Therefore, it is important for agency leaders to create a conducive work climate and apply a leadership style that can encourage employee enthusiasm and involvement to the maximum.